Innovation Networks and the New Asian Regionalism - Hans-Peter Brunner (Edward Elgar Publishing, 2016)
The rise of Asia, as well as the future of regional cooperation and integration (RCI) the world over, will be profoundly influenced by the challenges of slowing productivity growth, increasing economic inequalities and systemic vulnerabilities. Such structural reform issues will require RCI policies that complement domestic policy reform. This unique book explains what drives the regional economic integration of nations and their contribution to national knowledge capital. It also lays out how such beneficial integration can generate broad-based, equitable wealth in Europe and Asia.